Peran Orang Tua dalam Pembelajaran Daring Siswa Madrasah Ibtidaiyah Selama Transisi Pasca Pandemi (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
The transformation of the post-pandemic education system has crystallized online learning as a permanent component, with parents assuming an unprecedented instructional role at the elementary level, particularly at Madrasah Ibtidaiyah (MI). This qualitative case study aims to analyze in depth the dynamics and implications of the role of these parents during the transition period. Data was collected through in-depth interviews with parents, students, and teachers from two MIs in Blora, enriched by observation and analysis of communication documents. The findings of the study reveal three crucial things: first, there is a transformation of the role of parents into "substitute teachers" which creates a significant psychological burden due to the gap between the demands of the role and pedagogical capacity. Second, the communication pattern between schools and parents is still one-way and administrative, and has not built a collaborative three-way partnership by involving students. Third, the quality of parental assistance is very diverse and highly dependent on their digital literacy capacity and educational background, which directly affects the development of students' self-regulated learning. This study concludes that the effectiveness of parental roles is determined by psycho-educational support, the quality of communication channels, and the level of personal capacity, so policy implications must move towards a differentiated and empowerment-oriented approach.